Análisis de herramientas e-learning para el apoyo al proceso de enseñanza y aprendizaje en la unidad educativa réplica Eugenio espejo en el cantón Babahoyo, período 2023-2024 - Sandoval Uriarte, Teodora Elena (2023)
The Eugenio Espejo Educational Unit does not have a virtual technological tool, which hinders the teaching-learning process among students, teachers and school administrators. Investigating this Educational Unit and having a dialogue with several teachers, students and administrative staff, we determined that this problem exists because they do not have a virtual platform. In an environment where information and knowledge are increasingly digitized, the ability to access online educational resources and a more fluid interaction between students and teachers has become an important factor for educational success. The lack of a virtual platform not only reduces flexibility in the delivery of educational content, but can also impede communication and collaboration among all students and teachers in the educational institution, which can have a negative impact on students' learning outcomes and experiences. In addition, students could enjoy greater flexibility in their learning process, allowing them to progress at their own pace and access online resources to further their individual academic interests and needs. The proposal of analysis of the E-Learning digital platform can contribute to a better tripartite interaction, which speeds up and facilitates the work on this platform with all the benefits it generates, both for the authorities and the students, investigating this Educational Unit and having a dialogue with several teachers, students and administrative staff, we determined that there is this problem because they do not have a virtual platform